Graphene oxide: the new membrane material. Issue 1 (November 2015) - Joshi, R.K.; Alwarappan, S.; Yoshimura, M.; Sahajwalla, V.; Nishina, Y.
Abstract: A perfect molecular level separating unit for any kind of species to be filtered is on very high demand. In recent years, graphene oxide has emerged as an important material which can filter ions and molecules. This is an emerging field of research which has drawn extensive attention after the work by Nair et al.[1] . Following their work, various research groups started working in this area in last three years. Herein, we briefly review the recent development on graphene oxide membranes. This review is a summary of some very recent results and contributions made so far in this emerging research field. We have discussed recently developed mechanisms and models to understand the transport through GO based membranes. This review begins with a basic background on membrane technology followed by discussion related to developments of carbon materials based membrane technology. At the end we summarize advantages and disadvantages of membranes based on graphene oxide and discuss their future prospective.